Measuring Quality of Goods in Iran’s Intra-Industry Trade with G-8 Member States - Masoud Nonejad; Maryam Haghjoo (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2014)
As economic integration in East Asia progresses, trade patterns within region are displaying an ever–greater complexity. Although inter–industry trade still accounts for the majority, its share in overall trade is declining. Instead, intra–industry trade (IIT), which can be further divided into horizontal IIT (HIIT) and vertical IIT (VIIT) is growing in importance. In this paper, we set out and examine different kinds of intra-industry trade between Iran and G-8 member states by comparing the Greenway, Hine and Milner (1994) and Fontagne and Freudenberg (1997) approaches to disentangling vertical and horizontal intra–industry trade. Then we introduce and examine a new index from Azhar and Elliott to define product quality types between Iran and G-8 members for the time of 2001-2009. Result shows that a significant share of Iran’s industry trade with G-8 state members has been assigned to vertical intra industry trade. With regarded to Azhar and Elliott index, the main share of intra-industry trade consists of low quality goods.